2022
DOI: 10.1080/14760584.2022.2092472
|View full text |Cite
|
Sign up to set email alerts
|

Expert review on global real-world vaccine effectiveness against SARS-CoV-2

Abstract: IntroductionCOVID-19 vaccines have been highly effective in reducing morbidity and mortality during the pandemic. While primary series vaccination rates are generally high in Southeast Asian (SEA) countries, various factors have limited the rollout and impact of booster doses. Areas coveredWe reviewed 79 studies in the publicly available International Vaccine Access Center (IVAC) VIEW-hub platform on vaccine effectiveness (VE) after primary immunizations with two-dose schedules. VE data were reported for SARS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 68 publications
1
26
0
Order By: Relevance
“… 24 The equivalent VE observed for the main booster vaccines used in Thailand is consistent with a recent global analysis of VE data demonstrating equivalence of mRNA and vector vaccines as two dose schedules against earlier variants of concern. 13 This strongly suggests that accelerating booster vaccinations and increasing coverage by using any vaccines available, particularly among those aged 60 and older or those with co-morbidities is a valid strategy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 24 The equivalent VE observed for the main booster vaccines used in Thailand is consistent with a recent global analysis of VE data demonstrating equivalence of mRNA and vector vaccines as two dose schedules against earlier variants of concern. 13 This strongly suggests that accelerating booster vaccinations and increasing coverage by using any vaccines available, particularly among those aged 60 and older or those with co-morbidities is a valid strategy.…”
Section: Discussionmentioning
confidence: 99%
“…The most widely used vaccines in real world studies showed high and equivalent effectiveness, especially against severe COVID-19 outcomes. 13 Some studies have reported higher neutralizing-antibody response with heterologous boosters as compared to homologous boosters. 14 , 15 , 16 , 17 However, there is limited data available on the real-world vaccine effectiveness (VE) of heterologous schedules, particularly against the newer omicron variants.…”
Section: Introductionmentioning
confidence: 99%
“…Comparable protection from ChAdOx1 and P zer-BioNTech against infection has been previously reported. 10,16 Our data strongly suggests that accelerating the third and fourth dose vaccinations and increasing coverage by using any vaccines available, particularly among those aged 60 and older or those with comorbidities is an important strategy to optimize protection. Vaccination in addition to using personal protection measures such as wearing a mask, social distancing, and avoiding crowded settings, can help to reduce hospitalizations associated with omicron strain and, more importantly, mortality in the elderly or those with co-morbidities.…”
Section: Severe Covid-19 Outcomesmentioning
confidence: 91%
“…The initial clinical trials evaluated e cacy against early variants of concern, using homologous schedules, and high and equivalent effectiveness has been observed by the most widely used vaccines in real world studies, especially against severe COVID-19 outcomes. 10 Some studies have reported higher neutralizing-antibody response with heterologous boosters as compared to homologous boosters. [11][12][13] However, there is limited data available on the protective bene t of heterologous schedules, particularly against newer variants of concern.…”
mentioning
confidence: 99%
“…Although dozens of various reviews or meta-analyses have attempted to assess the effectiveness of vaccination against COVID-19 for different types of vaccines, [ 9 , 11 , 12 ], with regard to different coronavirus variants [ 9 , 11 , 13 , 14 ], risk groups [ 12 , 15 17 ], or the length of time after vaccination [ 15 , 18 ], no comprehensive study focused on the association of multiple factors with the vaccine effectiveness achieved has yet been published. Therefore, we decided to conduct a large meta-analysis extended with meta-regression referred to as “meta-COVANESS” (META-analysis/regression of COvid VAccine effectiveNESS) and to quantitatively evaluate the outcomes published during the first 2.5 years of immunization.…”
Section: Introductionmentioning
confidence: 99%